CHINESE FACTOR IN CAMBODIA AND ITS IMPACT ON VIETNAM - Khanh, Bui Nam (VNU Journal of Foreign Studies; Vol 35 No 5DO - 10.25073/2525-2445/vnufs.4421, 2019)
Cambodia is a neighboring country with a close history, a traditional partner and a potential commercial market, and it has have an important position in Vietnam’s foreign policy. Therefore, the study of assessing the “big country” in Cambodia, including China and the impact on Vietnam is very necessary in both scientific and practical aspects. Through a historical approach and on the basis of international relations analysis, the article analyzes why the Chinese factor has increased in Cambodia in recent years. How is China’s relationship with Cambodia in the fields of politics - diplomacy, economy, defense, security, culture and communication? The article also indicates that the Chinese factor will increase in Cambodia in the near future and evaluates the impact of this issue on Vietnam.